Finland : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper analyzes structural shocks, productivity, and growth in Finland. Finland has gone from being a top-performing advanced economy to a growth laggard since 2007. The rapid decline of the (previously) high productivity information and communications technology sector in recent years has weighed on overall growth and productivity. An analysis of industry-level data indicates that shifts in the sectoral distribution of labor and capital toward lower productivity sectors are also contributing to slower aggregate productivity growth. Firm-level analysis suggests that the aggregate total factor productivity impact of reallocating resources within sectors is limited, although there is more scope to reallocate resources between sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet